Atomic mass determination of uranium-238 - Kromer, Kathrin; Lyu, Chunhai; Bieroń, Jacek; Door, Menno; Enzmann, Lucia; Filianin, Pavel; Gaigalas, Gediminas; Harman, Zoltán; Herkenhoff, Jost; Huang, Wenjia; Keitel, Christoph H.; Eliseev, Sergey; et al. (Physical review, 2024)
The atomic mass of uranium-238 has been determined to be 238.050787618⁢(15) u, improving the literature uncertainty by two orders of magnitude. It is obtained from a measurement of the mass ratio of 238U47+ and 132Xe26+ ions with an uncertainty of 3.5×10−12. The measurement was carried out with the Penning-trap mass spectrometer Pentatrap and was accompanied by a calculation of the binding energies 𝐸U and 𝐸Xe of the 47 and 26 missing electrons of the two highly charged ions, respectively. These binding energies were determined using an ab initio multiconfiguration Dirac-Hartree-Fock method to be 𝐸U=39927⁢(10) eV and 𝐸Xe=8971.2⁢(21) eV. The new mass value will serve as a reference for high-precision mass measurements in the heavy mass region of the nuclear chart up to transuranium nuclides.
Gesehen am 21.06.2024